The influence of influencer experience, trustworthiness, attractiveness, content usefulness, price of product and product quality on purchase behavior in wardah consumers - Davis, Michael; Berlianto, Margaretha Pink (Enrichment : Journal of Management, 2025)
Product quality has a significant influence on purchasing behavior. The better the quality of Wardah beauty products, the more purchasing behavior on Wardah beauty products will increase, and vice versa, the worse the quality of Wardah beauty products, the more purchasing behavior will decrease. The results of this study are in accordance with previous research by Rahayu & Sudarmiatin (2022) showing that attractiveness has a significant influence on purchasing behavior. The results of this study are also in line with the statements of Rajalakshmi & Golden (2023) and Khasanah et al. (2023) showing that product quality can significantly influence consumer purchases. The cosmetics industry in Indonesia has always experienced significant growth and has the potential to have a large market in the ASEAN market, this potential then causes competitive market competition so it is important for managers to study consumer behavior. This study aims to test the effect of influencer experience, trust, attractiveness, content usefulness, product price and product quality on purchasing behavior in Wardah consumers. The study was conducted quantitatively on 177 respondents who were users of Wardah beauty products. The results of the study show that influencer experience, attractiveness and product quality have a significant influence on purchasing behavior, but influencer trust, influencer content usefulness and product price do not significantly influence purchasing behavior